Testing of the solar heat gain coefficient of fenestration product (2019)
https://content.sciendo.com/view/book/9788395669699/10.2478/9788395669699-013.xml DOI: https://doi.org/10.2478/9788395669699-013 9788395669699 https://creativecommons.org/licenses/by-nc-nd/4.0/legalcode